Effect of sugars on the thermal and rheological properties of sago starch - Fasihuddin B., Ahmad; Peter A., Williams (John Wiley & Sons Ltd, 1999)
Studies have been undertaken to investigate the effect of sugars on the thermal and rheological properties of sago starch. Sugars were found to increase the gelatinization temperature Tgel, and gelatinization enthalpy ΔH. Tgel and ΔH increased in the following order: control (water alone) < ribose < fructose < glucose < maltose < sucrose. The increase in ΔH was greater for 50% starch compared to 10% starch samples. The swelling factors in the presence of sugar were higher compared to the control for sugar concentrations below 25% but were lower at sugar concentration greater than 25%. These effects are discussed in terms of the antiplaticizing effect of the sugars compared to water, the influence of sugar–starch interactions and also the effect of the sugars on water structure. The storage modulus G′, the rate constant of gelation k, and the gel strength were significantly reduced in the presence of sugars. Generally G′ and k decreased in the following order: control (water alone) > hexose > disaccharide > pentoses. This has been attributed to the reduced proportion of amylose leached following gelatinizatison. In the presence of hexoses the freeze–thaw stability of starch gels decreased while in the presence of disaccharides and pentoses the freeze–thaw stability was slightly improved. © 1999 John Wiley & Sons, Inc. Biopoly 50: 401–412, 1999